An Update of Research Animal Models of Inflammatory Bowel Disease - Zineb Baydi; Youness Limami; Loubna Khalki; Nabil Zaid; Abdallah Naya; El Mostafa Mtairag; Mounia Oudghiri; Younes Zaid (The Scientific World Journal)
Inflammatory bowel disease (IBD) is a group of chronic disorders that includes two main disease forms, Crohn’s disease, and ulcerative colitis. The understanding of the intestinal inflammation occurring in IBD has been immeasurably advanced by the development of the now numerous murine models of intestinal inflammation. The usefulness of this research tool in IBD arises from a convergence of underlying genetic susceptibility, immune system dysfunction, environmental factors, and shifts in gut microbiota. Due to the multifactorial feature of these diseases, different animal models have been used to investigate the underlying mechanisms and develop potential therapeutic strategies. The results of preclinical efficacy studies often inform the progression of therapeutic strategies. This review describes the distinct feature and limitations of each murine IBD model and discusses the previous and current lessons from the IBD models.